Persepsi Masyarakat terhadap Political Branding Anggota DPRD Kota Bogor - Raja Aybeun Daffa Sayanda; Koesworo Setiawan; Robby Firliandoko (Institut Nalanda, 2026)
The low level of public trust in local legislative institutions poses a serious challenge to the democratic dynamics in Bogor City, as indicated by various fluctuating community satisfaction survey results. This research aims to analyze in depth the public perception of the political branding strategy carried out by members of The Bogor Parlementary as an effort to restore and increase public trust. Using the Brand Identity Prism theoretical framework developed by Jean-Noel Kapferer, this research dissects political identity through six main dimensions: physique, personality, culture, relationship, reflection, and self-image. The research method applied is descriptive qualitative, with primary data collection techniques through in-depth interviews with key informants in Tanah Sareal District, field observations, and documentation studies. The results showed that public perception of the subject's political branding tended to be positive in the external dimensions, where the subject was portrayed as a young, professional, neat, and communicative figure. However, in the internal dimension, public perception was found to be not optimal due to the lack of emphasis on Bogor's local cultural values and the existence of direct communication access barriers resulting from the use of intermediaries in constituent interactions. The conclusion of this study emphasizes that although the visual image has been well-formed, the level of public trust is still in a transitional stage. Strengthening the consistency between the identity displayed and the actual realization of political promises is needed to transform positive perceptions into stable and sustainable public trust.